Um estudo de caso sobre a diferença de entendimentos do Superior Tribunal de Justiça em relação à aplicabilidade do direito ao esquecimento. - Ferreira, Paulo Rafael de Lucena (2023)
The right to be forgotten is situated at a crossroads between privacy, freedom of expression, and access to information. This concept, already debated globally with doctrinal and jurisprudential origins from abroad, was subsequently introduced to Brazil. In Brazil, the right to be forgotten is intertwined with fundamental rights that protect one's personality and is anchored in the republic's principle of human dignity. However, its application in legal decisions has been inconsistent and controversial, leading to legal uncertainty. The Superior Court of Justice (STJ), a high-level Brazilian legal authority, has delivered varying verdicts in similar cases concerning this right, which, when likened to fundamental rights, should, in theory, be exercisable by all. This dissertation seeks to understand the reasons for these variations in the STJ's decisions based on two landmark cases decided in the same session by the same judges. For this purpose, the research was conducted using a methodology of embedded multiple-case studies, of an explanatory type, based on a primary methodological strategy of explanation construction, and a secondary one of analyzing embedded units. It is structured into four chapters: a deep dive into the right to be forgotten in international contexts, its adaptation in Brazil amidst the clash of fundamental rights, an overview of the case study methodology with its various applications and relevance to the study, and finally, an in-depth analysis of the cases leading to Special Appeals 1.334.097/RJ and 1.335.153/RJ. Finally, through the use of the case study methodology, it was demonstrated how the STJ presented a trajectory of different understandings based on delicate aspects involving the right to be forgotten in Brazil, enabling the response to the proposed objective.